Benchmarking memory and logic gates for trapped-ion quantum computing - Hughes, AC (2021)
Trapped ions are a promising platform for experimental quantum computing, possessing the longest decoherence times and the highest fidelity logic gates of any candidate technology. The challenge remains to scale up ion-trap systems to larger numbers of qubits. This thesis benchmarks two fundamental operations for scalable trapped-ion quantum computing: the memory performance of a 43Ca+ hyperfine qubit, and mixed-element entangling gates between 43Ca+ and 88Sr+.